Extensive lymphoid proliferation in syndromic multiple Odontogenic keratocysts—A unique finding. Issue 5 (September 2021) - Kaur, Harpreet; Mishra, Deepika; Bhutia, Ongkila
Abstract: We present the first and rare case report of syndromic multiple odontogenic keratocysts (OKCs) associated with extensive lymphoid proliferation. A 22-year-old male patient presented with radiolucent lesions in bilateral mandible and maxilla. Histopathology of the lesions showed features of multiple odontogenic keratocysts with reactive lymphoid proliferation. Additionally, presence of calcification of falx cerebri, palmar plantar pits and cervical scoliosis in the patient favored the diagnosis of nevoid basal cell carcinoma syndrome or Gorlin Goltz syndrome. Follow up after 2 years did not show any recurrence. Knowledge of this finding is important so that such entities are not confused with associated lymphoid neoplasms. Presence of lymphoid aggregates may be attributed to associated infection or remnants of cystic lining or breakdown products triggering cell mediated immunity leading to lymphoid hyperplasia.